Custo-efetividade dos medicamentos antipsicóticos utilizados para o tratamento da Esquizofrenia no Brasil - Andre Soares Santos (2016)
Schizophrenia is a chronic and debilitating disease that affects thought, affection and social conduct of patients. Schizophrenia affects between 0.3 and 3% of the population and apparently occurs in all countries with comparable prevalence rates. The treatment is performed with antipsychotic drugs. In Brazil, the standard drugs for the treatment of schizophrenia, in Sistema Único de Saúde, are: haloperidol, chlorpromazine, risperidone, ziprasidone, olanzapine, quetiapine and clozapine. The aim of this study is to evaluate the cost-effectiveness of antipsychotic drugs, from the perspective of , in order to provide information for evidence-based decisions for the treatment of schizophrenia in Brazil. A systematic review of economic evaluations and a cost-effectiveness analysis were conducted. For the cost-effectiveness analysis, a Markov model was built with 18 months of time horizon and considering discontinuation of treatment for any cause as a measure of effectiveness. The analysis of the systematic review of economic evaluations showed that the drugs used in the SUS more commonly considered cost-effective in international studies are risperidone, olanzapine and clozapine. The sensitivity analysis showed robustness in results in relation to the source of funding for the study. The analysis of the cost-effectiveness study between olanzapine, risperidone, quetiapine and ziprasidone leads to the conclusion, considering the outcome of treatment discontinuation, that olanzapine is dominant over the alternatives evaluated.